Analisis Yuridis Sistem Pencegahan Kecurangan (Fraud) Di Fasilitas Kesehatan Dalam Penyelenggaraan Program Jaminan Kesehatan Nasional Di Indonesia - Maya Febriyanti Purwandari; Efrila; Edwin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Expert opinion states that fraud in the implementation of JKN is an act carried out deliberately to obtain financial benefits from the health insurance program in the National Social Security System through fraudulent acts that are not in accordance with the provisions. Various forms of similar fraud will be able to color in health social insurance claims, which can be carried out by individuals or groups or by Health Service Providers at the first level or hospitals as referral recipients. This form of fraud can occur due to the incomprehension of the community of health service users or carried out by KDP because medical expenses are borne by the insurer. In addition to threatening the sustainability of the JKN program itself, fraud also harms many parties including the general public, patients, medical personnel, hospitals and the government. The general public also bears higher premiums and smaller benefits due to budget leaks. Patients may also be disadvantaged by substandard services and episode breakdown of services. To analyze the application of fraud prevention systems in the implementation of the National Health Insurance Program and to conduct a legal model analysis in preventing Deviation or Fraud in the Implementation of the National Health Insurance Program